TEORI MANAJEMEN SARANA PRASARANA - Saputra, Alan Lutfi Gesang; Sriyanto, Agus (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2021)
Education encompasses more than just learning, while learning is an integral element of it. Simply said, education is an intentional and conscious endeavor to mature through the transmission of ideals to students. Management of educational facilities and infrastructure can be defined as the process of successfully and efficiently utilizing all educational facilities and infrastructure. Educational facility and infrastructure management is responsible for managing and maintaining educational facilities and infrastructure in order for them to contribute maximally to the educational process. The purpose of educational facility and infrastructure management is to plan a thought process.